Review of semiconductor devices and other power electronics components at cryogenic temperature - Yuchuan Liao; Abdelrahman Elwakeel; Yudi Xiao; Rafael Peña Alzola; Min Zhang; Weijia Yuan; Alfonso J. Cruz Feliciano; Lukas Graber (iEnergy, 2024)
With the increasing demand for high power density, and to meet extreme working conditions, research has been focused on investigating the performance of power electronics devices at cryogenic temperatures. The aim of this paper is to review the performance of power semiconductor devices, passive components, gate drivers, sensors, and eventually power electronics converters at cryogenic temperatures. By comparing the physical properties of semiconductor materials and the electrical performance of commercial power semiconductor devices, silicon carbide switches show obvious disadvantages due to the increased on-resistance and switching time at cryogenic temperature. In contrast, silicon and gallium nitride devices exhibit improved performance when temperature is decreased. The performance ceiling of power semiconductor devices can be influenced by gate drivers, within which the commercial alternatives show deteriorated performance at cryogenic temperature compared to room temperature. Moreover, options for voltage and current sense in cryogenic environments are justified. Based on the cryogenic performance of the various components afore-discussed, this paper ends by presenting an overview of the published converter, which are either partially or fully tested in a cryogenic environment.